Returns to managerial ability and technical efficiency in Argentina dairy farms - Gallacher, Marcos; Lema, Rolando Daniel (International Association of Agricultural Economists, 2021)
This paper explores the returns to managerial ability and his role in determining efficiency in Argentina dairy farms. Using an unbalanced panel data from 2003 through 2009 we estimate production frontiers and technical efficiency effects. Most studies analyzing the impact of human capital in agriculture use the measure of years of schooling of the producer as a proxy for decision-making skills. An alternative measure is used in this paper. The measure was derived by “grading” decision-making and execution skills of the farmers. Grades were assigned by farm advisors knowledgeable of each farm and producer characteristics. Assigned grades were then used in the production frontiers as inputs to estimate the impact of management skills on firm-level results. A very significant impact of these skills on firm results and on technical efficiency and was found.